Colonization and extinction dynamics of a declining migratory bird are influenced by climate and habitat degradation. (23rd June 2014) - Mustin, Karen; Amar, Arjun; Redpath, Stephen M.; Bauer, Silke
<x xml:space="preserve">Abstract</x> Uncovering the mechanisms involved in the decline of long‐distance migrants remains one of the most pressing issues in European conservation. Since the 1980s, the British breeding population of Garden Warbler Sylvia borin has declined by more than 25%. Here we use data from repeated bird surveys of woodland sites in the 1980s and in 2003–2004 to show that, although the overall population declined between the two periods, the probability of occupancy for this species increased at high latitudes and decreased at low latitudes. Range shifts such as this arise from a change in the ratio of colonizations to extinctions at the range margins, and we therefore related colonization and local extinction at the patch level to concurrent changes in temperature and habitat. The probability of patch colonization by this species was significantly lower where the percentage cover of vegetation in the understorey had declined, reducing habitat quality for this species. The probability of local extinction was significantly correlated with increasing mean May temperature, which may reflect a change in phenology, making breeding conditions less suitable. Changed regimes of grazing and woodland management could be used to increase habitat suitability and thereby increase colonization probability at the local scale, which may in turn increase the probability of patch occupancy despite future climatic unsuitability.